Measuring non-vitamin K antagonist oral anticoagulant levels: When is it appropriate and which methods should be used? - Drouet, Ludovic; Steiner, Thorsten; Purrucker, Jan (International journal of stroke, 2016)
BackgroundAlthough the need for an emergency intervention may merit laboratory measurement of non-vitamin K antagonist oral anticoagulant (NOAC) concentration or anticoagulant activity, NOACs are not supposed to require routine monitoring due to their stable pharmacological profiles compared with warfarin.AimsTo examine situations where NOAC measurement may be useful and to provide information about methodologies available to measure NOAC-related anticoagulation activity.Summary of reviewThe routine coagulation tests, including prothrombin time, thrombin time, activated partial thromboplastin time, and international normalized ratio, have variable sensitivities to NOACs. Tests have been developed for use with specific NOACs, e.g. diluted thrombin time or chromogenic factor Xa assays. In emergency situations, such as severe bleeding, stroke, or a requirement for urgent surgery or procedures, there may be a need to assess anticoagulant activity to guide clinical decision making. In cases where neutralization of the anticoagulant effect is warranted, specific reversal agents are likely to become invaluable medical tools. Evidence to date suggests that dosing decisions for NOACs based on clinical features (e.g. age or renal function) can help optimize the benefit?risk balance without assessment of anticoagulant activity in non-emergency routine situations.ConclusionsRegular monitoring of NOAC levels does not provide benefits and cannot be recommended at present. In some specific circumstances, e.g. severe bleeding, before urgent surgery, or before thrombolysis, measurement may be beneficial to assess whether a patient is actively anticoagulated. The availability of NOAC-specific reversal agents may change management practices in emergencies.
Gesehen am 06.12.2017